Development of a high-rate scalable readout system for gaseous detectors. (1st December 2022) - Scharenberg, L.; Bortfeldt, J.; Brunbauer, F.; Christensen, M.J.; Desch, K.; Flöthner, K.; Garcia, F.; Janssens, D.; Kaminski, J.; Lisowska, M.; Lupberger, M.; Muller, H.; et al.
Abstract: The RD51 collaboration developed the Scalable Readout System (SRS) as part of its R&D activities on Micro-Pattern Gaseous Detectors. This common multi-purpose readout system allows to read out small R&D detectors (0.2k channels) up to mid-sized experiments with multiple detectors (2.5k to 5k channels). To cope with increased demands on detectors, electronics and readout speed, a new front-end ASIC—the VMM3a—was integrated into the SRS. This led to the development of a scalable, self-triggered high-rate readout system that provides energy, space and time information of the interacting particles at the same time.